Institutional Credibility and Foreign Investment: Lessons from Indonesia’s Regulatory Transformation - Vina Apriliani Su’udiah; Pilifus Junianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research explores the role of institutional credibility and government policies in attracting Foreign Direct Investment (FDI) to Indonesia. As a developing economy, Indonesia's ability to attract foreign investment is influenced by factors such as regulatory frameworks, political stability, and infrastructure. However, challenges such as bureaucratic inefficiencies and policy inconsistencies hinder FDI growth. The problem addressed in this study is understanding how institutional credibility and government initiatives affect the flow of FDI into Indonesia. The primary objectives of the research are to analyze the impact of institutional credibility on FDI, examine the role of government policies in enhancing the investment climate, and identify areas for improvement in attracting foreign capital. A qualitative research method was employed, utilizing document analysis of government reports and policy documents, as well as in-depth interviews with key informants, including policymakers, business leaders, and economists specializing in FDI. The results show that transparent, consistent, and predictable policies significantly boost investor confidence, while bureaucratic inefficiencies and inconsistent regulations remain barriers. Additionally, tax incentives, regulatory simplification, and infrastructure development have a positive impact on attracting foreign investment. The study concludes that Indonesia must prioritize policy consistency, improve bureaucratic efficiency, and continue to invest in infrastructure to enhance its competitiveness in the global investment market.